Proposta de estrutura de trabalho para aumentar a eficiência das compras públicas compartilhadas - Nascimento, Wesley Ribeiro do (2015)
The public procurement environment moves most of the Brazilian public resources. Working with the adoption of measures reducing costs becomes increasingly determinants in an environment of cost containment and reduction of costs. For such, shared procurement emerge as source of optimization of efforts between public agencies managers and participants of this form of procurement. The use of bidding per prices registry facilitates the acquisition shared, using the tools available in the portals of public purchases. The main objectives of this research were the identification and definition of the dysfunctions, developing a structure of work for the improvement of the performance of shared purchases, and the appointment of assignments for the application of the methods that result from the search. The adoption of measures for the promotion of improvements in the planning of activities related to the treatment of public shared acquisitions was the one that presented more impact on the promotion of purchases, being responsible for highlighting such a method. Thus, it was possible to determine the planning as vital for the shared acquisition, where the approximation of institutions involved is the main form of success in promoting the method